Endovascular Repair of Aortobronchial Fistula after Bentall Procedure. (3rd April 2018) - Gruenebaum, Dane D.; Graf, Ray; Alexander, Thomas; Tavares, Sergio; Surani, Salim
Abstract : Aortobronchial fistula (ABF) is a rare complication of aortic repair seen with both surgical and endovascular manipulation. The available literature largely refers to the need for surgical repair. We are not aware of any reports of endovascular repair after the Bentall procedure. This report describes a patient who after the Bentall procedure presented with massive hemoptysis from ABF, a multidisciplinary team decided on endovascular repair due to patient frailty to avoid redo sternotomy. We believe this is the first case report of endovascular repair and represents the success of multidisciplinary collaboration.